Comparison between scheduling techniques in long term evolution - Habaebi, Mohamed Hadi; Chebil, Jalel; Al-Sakkaf, A.G.; Dahawi, T. H. (IIUM Press, 2013)
Long-Term Evolution (LTE) is a recently evolving technology characterized by very high speed data rate that allows users to access internet through their mobile as well as through other electronic devices. Such technology is intended to support variety of IP-based heterogeneous traffic types. Traffic scheduling plays an important role in LTE technology by assigning the shared resources among users in the most efficient manner. This paper discusses the performance of three types of scheduling algorithms namely: Round Robin, best Channel Quality Indicator (CQI) and Proportional Fair (PF) schedulers representing the extreme cases in scheduling. The scheduling algorithms performances on the downlink were measured in terms of throughput and block error rate using a MATLAB-based system level simulation. Results indicate that the best CQI algorithm outperforms other algorithms in terms of throughput levels but on the expense of fairness to other users suffering from bad channel conditions.